The woman king [videorecording (Blu-Ray)] - Stevens, Dana, 1963-; Bello, Maria, 1967-; Davis, Viola, 1965-; Mbedu, Thuso; Lynch, Lashana, 1987-; Atim, Sheila, 1992-; Fiennes-Tiffin, Hero; Boyega, John (Sony Pictures Home Entertainment, 2022)
The remarkable story of the Agojie, the all-female unit of warriors who protected the African Kingdom of Dahomey in the 1800s with skills and a ferocity unlike anything the world has ever seen. Inspired by true events, it follows the emotionally epic journey of General Nanisca as she trains the next generation of recruits and prepares them for battle against an enemy determined to obliterate their way of life. Some things are worth fighting for.